Wearable Technologies in School Physical Education: A Systematic Review of Pedagogical Implications - Zhao, Zuoxian; Su, Yingxue (Physical Education Theory and Methodology, 2026)
Background. Wearable technologies such as heart rate monitors, accelerometers, and fitness trackers are increasingly integrated into school-based physical education (PE) to enhance instructional strategies, student engagement, and personalised learning. Yet empirical evidence on their pedagogical effectiveness remains fragmented. Purpose. This systematic review synthesises research on wearable technology applications in school-based PE, examining their integration into teaching strategies, student motivation and participation, and personalised feedback. Methods. A systematic search across Web of Science, Scopus, ERIC, SPORTDiscus, and PsycINFO identified 12 peer-reviewed studies published between 2010 and 2025. Methodological quality was assessed using the Mixed Methods Appraisal Tool (MMAT), and results were synthesised narratively. Results. Wearable technologies facilitated diverse instructional strategies including real-time feedback, self-monitoring, gamification, and goal setting. Their use increased student motivation, participation, and enabled personalised feedback, although data privacy and ethical concerns were noted. Teacher digital literacy and pedagogical competence influenced implementation effectiveness. Conclusions. Wearable technologies offer significant pedagogical benefits for school-based PE by enhancing motivation, participation, and personalisation. Successful implementation requires thoughtful instructional design, teacher readiness, and careful ethical management of student data. Future research should investigate long-term outcomes and professional development models for educators.